2021
DOI: 10.1111/jth.15236
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological targeting of coagulation factor XI mitigates the development of experimental atherosclerosis in low‐density lipoprotein receptor‐deficient mice

Abstract: Background: Human coagulation factor (F) XI deficiency, a defect of the contact activation system, protects against venous thrombosis, stroke, and heart attack, whereas FXII, plasma prekallikrein, or kininogen deficiencies are asymptomatic. FXI deficiency, inhibition of FXI production, activated FXI (FXIa) inhibitors, and antibodies to FXI that interfere with FXI/FXII interactions reduce experimental thrombosis and inflammation. FXI inhibitors are antithrombotic in patients, and FXI and FXII deficiencies are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 54 publications
0
37
0
Order By: Relevance
“… 39 Further emphasizing the central role of FXII in mediating atherothrombosis, deficiency of FXII or FXIIa inhibition has been demonstrated to diminish thrombus formation on atherosclerotic plaque material ex vivo. 40 Moreover, a recent study investigating pharmacological inhibition of FXI not only implicated FXI/FXIa in the development of atherosclerosis and thereby indirectly supporting the pathological role of FXIIa within the plaque confines, 41 but also provides further evidence that therapeutic targeting of coagulation factors holds immense potential to impact cardiovascular clinical outcomes.…”
Section: Discussionmentioning
confidence: 97%
“… 39 Further emphasizing the central role of FXII in mediating atherothrombosis, deficiency of FXII or FXIIa inhibition has been demonstrated to diminish thrombus formation on atherosclerotic plaque material ex vivo. 40 Moreover, a recent study investigating pharmacological inhibition of FXI not only implicated FXI/FXIa in the development of atherosclerosis and thereby indirectly supporting the pathological role of FXIIa within the plaque confines, 41 but also provides further evidence that therapeutic targeting of coagulation factors holds immense potential to impact cardiovascular clinical outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…The 5 mg/kg dosage of 14E11 was chosen based on previous work that showed that 14E11 decreased murine FXI levels below the limit of detection. 8 In brief, the dose-finding experiment was performed wherein C57BL/6 mice were injected with a single subcutaneous (SC) dose of 14E11 (5 mg/kg) and APTT was monitored over a period of 10 days. Mice in this study were injected with a single SC dose of 14E11 (5 mg/kg) immediately before inferior vena cava (IVC) constriction surgery.…”
Section: Essentialsmentioning
confidence: 99%
“…7 Previous studies have highlighted the roles of FXI and the contact pathway of coagulation in mediating inflammation in various models of disease. [8][9][10][11] In a mouse model of sepsis, contact pathway inhibition after cecal ligation and perforation was protective and increased survival. 10 Similarly, in a baboon model of Staphylococcus aureus induced sepsis, inhibition of FXI activation by FXIIa attenuated the inflammatory cytokine surge and reduced organ failure and mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze HUVECs permeability to BSA, media containing Evans Blue dye (0.67 mg/ml) and 4% BSA was added to the upper chamber for 30 min at 37°C. Samples from the lower chamber were collected and absorbance at 650 nm was measured using a spectrophotometer (Tecan) as previously described (50).…”
Section: Permeability In Transwell Assaymentioning
confidence: 99%